3% nebulized hypertonic saline versus normal saline for infants with acute bronchiolitis: A systematic review and meta-analysis of randomized controlled trials. Issue 43 (28th October 2022) - Yu, Jin-Feng; Zhang, Yan; Liu, Zhan-Bo; Wang, Jing; Bai, Li-Ping
Abstract : Background: This study evaluated the efficacy and safety of 3% nebulized hypertonic saline (NHS) in infants with acute bronchiolitis (AB). Methods: We systematically searched the PUBMED, EMBASE, Cochrane Library, China National Knowledge Infrastructure Database, WANFANG, and VIP databases from inception to June 1, 2022. We included randomized controlled trials comparing NHS with 0.9% saline. Outcomes included the length of hospital stay (LOS), rate of hospitalization (ROH), clinical severity score (CSS), rate of readmission, respiratory distress assessment instrument, and adverse events. RevMan V5.4 software was used for statistical analysis. Results: A total of 27 trials involving 3495 infants were included in this study. Compared to normal saline, infants received 3% NHS showed better outcomes in LOS reduction (MD = −0.60, 95% CI [−1.04, −0.17], I 2 = 92%, P = .007), ROH decrease (OR = 0.74, 95% CI [0.59, 0.91], I 2 = 0%, P = .005), CSS improvement at day 1 (MD = −0.79, 95% CI [−1.23, −0.34], I 2 = 74%, P < .001), day 2 (MD = −1.26, 95% CI [−2.02, −0.49], I 2 = 91%, P = .001), and day 3 and over (MD = −1.27, 95% CI [−1.92, −0.61], I 2 = 79%, P < .001), and respiratory distress assessment instrument enhancement (MD = −0.60, 95% CI [−0.95, −0.26], I 2 = 0%, P < .001). No significant adverse events related to 3% NHS were observed. Conclusion: This study showed that 3% NHS was better than 0.9% normal saline in reducing LOS, decreasing ROH, improving CSS, and in enhancing the severity of respiratory distress. Further studies are needed to validate these findings.